Salinitas dan Flake Serasah Daun Mangrove yang Berbeda Mempengaruhi Pertumbuhan (Dendronereis pinnaticiris) - Hartanti, Ninik Umi; ,, Suyono (OSEATEK, 2015)
Result of the research showed that leaf litter of A. Marina contained 19.48% which was higher than that of R. stylosa that contained 5,86%, while R. stylosa contained lipid of 2.31 % dry weight, which was higher than that of A marina that contained lipid of 1.96 % dry weight. R. stylosa contained the highest fibre. Survival rate of PlS1 66.667 %, P1S2 100 %, P2S1 100 %, P2S2 100%, P3S1 was 100% and P3S2 was 100%. The different feed types affected body weight increment, where P1S1 was 0 mg, PlS2 was 227 mg, P2S1 was 27,9 mg P2S2 was 143 mg and P3S1 was 134 mg and P3S2 was 93 mg. The average number of  posterior segment generated was P1S1 (5,08), P1S2 (59,8), P2S1 (18,33), P2S2 (47,7) and P3S1 (40) P3S2 (33,5). Feeding artificial diet made from leaf mangrove litter as raw material increased growth but did not increase survival rate of the worm. Growth of the nereid worm fed with flake composed from leaf litter of A marina anda 30 ppt salinity was greater than that fed with flake made of leaf litter another and the mixture of leaf litter of both mangrove plant species.Key Word : nereid worm, leaf litter of mangrove plant, feed